A novel therapeutic vaccine composed of a rearranged human papillomavirus type 16 E6/E7 fusion protein and Fms-like tyrosine kinase-3 ligand induces CD8+ T cell responses and antitumor effect. Issue 47 (7th November 2017) - Li, Jianqiang; Chen, Si; Ge, Jun; Lu, Feng; Ren, Sulin; Zhao, Zhiqiang; Pu, Xiuying; Chen, Xiaoxiao; Sun, Jiaojiao; Gu, Yueqing
Highlights: A novel vaccine includes rationally shuffled HPV16 E6/E7 fusion protein and Flt3L. Mutant and rearrangement are carried on E6/E7 protein to enhance immunogenicity. Linking Flt3l could efficiently enhance the E7-specific CD8 + T cell response. Flt3L-RM16 significantly induces CD8 + T cell responses and antitumor effect. Abstract: The development of cervical cancer is mainly caused by infection with high risk genotypes of human papillomavirus, particularly type 16 (HPV16), which accounts for more than 50% of cervical cancer. The two early viral oncogenes, E6 and E7, are continuously expressed in cervical cancer cells and are necessary to maintain the malignant cellular phenotype, thus providing ideal targets for immunotherapy of cervical cancer. In this study, a novel vaccine strategy was developed based on a rationally shuffled HPV16 E6/E7 fusion protein, the addition of Fms-like tyrosine kinase-3 ligand (Flt3L) or the N domain of calreticulin (NCRT), and the usage of a CpG adjuvant. Four recombinant proteins were constructed: m16E6E7 (mutant E6/E7 fusion protein), rm16E6E7 (rearranged mutant HPV16 E6/E7 fusion protein), Flt3L-RM16 (Flt3L fused to rm16E6E7), and NCRT-RM16 (NCRT fused to rm16E6E7). Our results suggest that Flt3L-RM16 was the most potent of these proteins in terms of inducing E6- and E7-specific CD8 + T cell responses. Additionally, Flt3L-RM16 significantly induced regression of established E6/E7-expressing TC-1 tumors. Higher doses of Flt3L-RM16 trended toward higher levels of antitumor activity, but these differences did not reach statistical significance. In summary, this study found that Flt3L-RM16 fusion protein is a promising therapeutic vaccine for immunotherapy of HPV16-associated cervical cancer.